Sexual violence from police and HIV risk behaviours among HIV‐positive women who inject drugs in St. Petersburg, Russia – a mixed methods study. (18th July 2016) - Lunze, Karsten; Raj, Anita; Cheng, Debbie M; Quinn, Emily K; Lunze, Fatima I; Liebschutz, Jane M; Bridden, Carly; Walley, Alexander Y; Blokhina, Elena; Krupitsky, Evgeny; Samet, Jeffrey H
Abstract : Introduction: Police violence against people who inject drugs (PWID) is common in Russia and associated with HIV risk behaviours. Sexual violence from police against women who use drugs has been reported anecdotally in Russia. This mixed‐methods study aimed to evaluate sexual violence from police against women who inject drugs via quantitative assessment of its prevalence and HIV risk correlates, and through qualitative interviews with police, substance users and their providers in St. Petersburg, Russia. Methods: Cross‐sectional analyses with HIV‐positive women who inject drugs ( N =228) assessed the associations between sexual violence from police (i.e. having been forced to have sex with a police officer) and the following behaviours: current drug use, needle sharing and injection frequency using multiple regression models. We also conducted in‐depth interviews with 23 key informants, including PWID, police, civil society organization workers, and other stakeholders, to explore qualitatively the phenomenon of sexual violence from police in Russia and strategies to address it. We analyzed qualitative data using content analysis. Results: Approximately one in four women in our quantitative study (24.1%; 95% CI, 18.6%, 29.7%) reported sexual violence perpetrated by police. Affected women reported more transactional sex for drugs or money than those who were not; however, the majority of those reporting sexual violence from police were not involved in these forms of transactional sex. Sexual violence from police was not significantly associated with current drug use or needle sharing but with more frequent drug injections (adjusted incidence rate ratio 1.43, 95% CI 1.04, 1.95). Qualitative data suggested that sexual violence and coercion by police appear to be entrenched as a norm and are perceived insurmountable because of the seemingly absolute power of police. They systematically add to the risk environment of women who use drugs in Russia. Conclusions: Sexual violence from police was common in this cohort of Russian HIV‐positive women who inject drugs. Our analyses found more frequent injection drug use among those affected, suggesting that the phenomenon represents an underappreciated human rights and public health problem. Addressing sexual violence from police against women in Russia will require addressing structural factors, raising social awareness and instituting police trainings that protect vulnerable women from violence and prevent HIV transmission.